BEHAVIORAL FACTORS OF POST PARTUM MOTHERS ABOUT BABY MASSAGE AT SALLY CLINIC MEDAN IN 2024 - Karsana, Karsana; Violent, Violent (Benih : Journal of Midwifery, 2024)
Every parent expects their child to grow and develop optimally, so that they can0 become quality and resilient human resources. Baby massage can increase weight, baby growth, baby's immune system and strengthen the affection between parents and children. This study is analytical in nature, namely to determine the Behavioral Factors of Pregnant Women About Baby Massage. The research was conducted in November 2023-January 2024. The population in this study were all postpartum mothers at the Sally Medan Clinic. The results of this study indicate that the highest Behavioral Factors of postpartum mothers about baby massage are Behavioral Factors in the good category of 16 respondents (53.33%), Behavioral Factors are sufficient 11 respondents (36.67%) and Behavioral Factors are lacking 3 respondents (10%). Behavioral Factors of postpartum mothers about baby massage based on age are highest at the age of 20-35 years as many as 26 people (86.67%), with good knowledge as many as 14 respondents (46.67%), sufficient knowledge as many as 11 respondents (36.67%) and those with less knowledge 1 respondent (3.33%). Postpartum mothers' behavioral factors about baby massage based on education, the highest was high school education of 14 respondents (46.67%), while in the lowest group in junior high school with less knowledge of 1 respondent (3.33%). And the highest behavioral factors of pregnant women based on parity were multiparas of 15 respondents (10%), those with good knowledge were 8 respondents (26.66%), those with sufficient knowledge were 7 respondents (23.34%) and those with less knowledge were none. From the results of this study, it is expected that parents can increase their knowledge about baby massage, and can do baby massage themselves at home.